Evaluation of the Effectiveness of the Use of LQR-LQT Control System on DC Motor Dunkermotor GR30X10 for Energy Efficiency Improvement in Technology-Based Community Empowerment Program in Village X with SISO Approach Using MATLAB Simulink - Mochammad Nawal Gibran (Maritime in Community Service and Empowerment, 2023)
This paper presents a modeling of the LQR and LQT control systems simulated in a SISO (Single Input, Single Output) setup using MATLAB Simulink. The simulation is conducted on wireless communication signals, where the input signal transmitted is expected to match the output at the receiver. However, during data transmission, disturbances such as noise often occur, which are typically outside the sender's control. Therefore, this research explores the differences between a standard SISO system and one that includes noise disturbances. The findings are significant in demonstrating the effect of noise on the efficiency of communication systems and how advanced control methods like LQR and LQT can be utilized to mitigate the impact of such disturbances in real-world applications, particularly in the context of community empowerment programs. These programs leverage technological innovations to optimize energy usage and improve productivity in rural areas.